Working conditions in a mental health institution: An exploratory study of professional nurses in Limpopo province, South Africa - Ndivhuwo P. Mulaudzi; Ntsieni S. Mashau; Henry A. Akinsola; Tinotenda S. Murwira (AOSIS, 2020)
Background: Professional nurses are responsible for the provision of care, treatment and rehabilitation of all mental healthcare users (MHCUs) in the institutions for mental healthcare. However, professional nurses find themselves in difficult circumstances under which they must provide quality healthcare services to MHCUs. Objectives: The study explored and described the challenges experienced by the professional nurses working in a mental healthcare institution in Limpopo province of South Africa. Method: A qualitative approach was used to explore and describe the challenges faced by professional nurses working in a mental healthcare institution. The study was conducted from July 2016 to December 2016. Purposive sampling was used to select participants. Data were obtained through individual in-depth interviews with professional nurses between the ages of 26 and 50 years. Data collection continued until data saturation, which occurred after interviewing 18 participants. Tech's open coding method was used to analyse data in this study. Results: Four themes emerged from data analysis, namely: inadequate safety measures, inadequate resources, impact of high workload and shortage of staff. The themes were further sub-divided into sub-themes. Conclusion: The study revealed several challenges that professional nurses face in mental healthcare institutions which might be a barrier to the provision of quality healthcare. Conducive working environments should be established to enable professional health nurses to provide quality nursing care, thereby promoting the health of MHCUs.